Nilai Pendidikan Karakter dalam Ragam Gerak Tari Mayang Rontek Kabupaten Mojokerto - Leni Nur Halita (Gelar : Jurnal Seni Budaya, 2020)
This study aims to determine the value of character education contained in the meaning of the variety of movements Mayang Rontek Dance Mojokerto district. This research is a qualitative research with a descriptive approach. The object of this study is the variety of movements Mayang Rontek Dance. The data source of this research was obtained from primary data sources, namely the results of observing the variety of movements of Mayang Rontek Dance through video of Mayang Rontek DIYoutube, as well as secondary data sources obtained from the collection of journals, books on Mayang Rontek Dance, and other documents containing analysis of research conducted. Data collection techniques through literature study. Literature study is conducted to obtain existing data, either in the form of photos, videos or other documents related to the research object to be examined. Analysis techniques include analyzing data, presenting data, and concluding. The results of the various movements of the Mayang Rontek Dance show that this dance contains the value of character education which is depicted in various movements of the Mayang Rontek Dance. Some of the various movements include Melampah Songgo Nompo, bukak nggawar kanan dan kiri, mlampah ngloro, mentang nggawar, nogo mangap, mlampah prapatan, kencrongan, bedhayan gajah oling, tmpang tali jombangan, dan lembeyan. The meaning of the movement consists of: 1) About sincerity and gratitude to God Almighty, 2) about human problems and their resolution, 3) about human life will not always be smooth, and 4) about humans having good, bad, and own attitudes lust.